Learning leadership? Elite Ugandan students and late colonial politics. (16th January 2019) - Summers, Carol
Abstract: In Uganda, teaching and learning were important metaphors for colonial rule, suggesting a benign protectorate under Britain's guidance. Ugandans, though, repurposed images of teaching, studying and educational sponsorship. Drawing on indigenous ideas about effective education as a sort of experiential education in leadership, they perceived student activism as a resource for a new political and social system. Articulate Ugandans sought elite British education as a weapon. Others emphasized the harsh competitiveness of Uganda's elite schools as the basis for new class solidarities. And educated men saw their ownership of schools as a foundation on which to build political followings as they worked to guide the country. Student activism in Uganda emphasized educated Ugandans' individual and collective practice in power and leadership. Résumé: En Ouganda, enseigner et apprendre étaient des métaphores importantes du régime colonial, suggérant un protectorat bienveillant sous la houlette britannique. Or, les Ougandais réapproprièrent l'image de l'enseignement, des études et du mécénat pédagogique. S'appuyant sur l'idée indigène d'une éducation efficace qui serait une sorte d'éducation expérientielle en leadership, ils percevaient l'activisme étudiant comme une ressource promotrice d'un nouveau système politique et social. Les Ougandais éloquents convoitaient l'éducation prestigieuse britannique pour s'en faire une arme. D'autres mettaient l'accent sur la compétitivité acharnée des écoles prestigieuses ougandaises comme le fondement à de nouvelles solidarités de classes. Et les hommes instruits voyaient dans le fait de posséder des écoles un moyen d'entretenir un terreau de partisans politiques, dans leur quête de donner une orientation au pays. L'activisme étudiant en Ouganda soulignait la pratique individuelle et collective du pouvoir et du leadership par les Ougandais instruits.